Scale-up of the film coating process using the example of vitamin and mineral complexes: from idea to process validation - A. V. Strelkova; E. V. Flisyuk (Разработка и регистрация лекарственных средств)
Introduction. The development of defect-free film coating modes is an urgent task when transferring film-coated tablets technology. Technology transfer is an integral stage of the life cycle of any drug approved for industrial production. During the development of the technological process, deviations may occur, to eliminate which it is necessary to introduce auxiliary operations or change the chain of technological equipment.Aim. Optimize the process of applying a film coating to tablets of the core of the vitamin and mineral complex.Materials and methods. The objects of the study were biconvex core tablets in the form of a boat of a vitamin and mineral complex consisting of vitamins C + E + B1 and minerals. To ensure the required technological properties, auxiliary substances were used: microcrystalline cellulose, sodium croscarmellose, potato starch, calcium stearate, colloidal silicon dioxide. Ready-made film-forming mixtures (Colorcon®) in beige Opadry® II 85F 270000 were used as film-forming compositions. The film coating was applied in the craters with a perforated drum BG-80 (Pro-face, China) and BGK-150 (Zhejiang Canaan Technology Limited, China).Results and discussion. The process of applying a film coating to the core tablets of a vitamin and mineral complex has been studied. The analysis of the current technological chain showed a number of disadvantages – a large amount of manual labor, the need for matting the drum, the duration of the process, low loading, braking of the production cycle due to lagging at the stage of applying the film shell. To solve the discovered problems, a project was developed to scale the technology at the stage of applying a film shell to tablets-the cores of a vitamin and mineral complex. During the implementation of the process, new equipment was purchased and installed for production. The development of the technological process made it possible to multiply the one-time loading into the boiler (by 2–3 times), automate the process due to the automatic operation function according to the parameters set before the start of the technological process, and exclude the matting of the drum from preparatory work. The quality of film-coated tablets has improved, and the risk of defects has significantly decreased.Conclusion. During the study, it was proved that transferring the film coating process to another piece of equipment can improve the quality of the resulting film-coated tablets and optimize the technological process. A multiple increase in the loading size is not carried out at the same time by changing the number of nozzles and the inner section of the hose for applying the film coating material.